HUBUNGAN ASAM LEMAK RANTAI PENDEK, STRATIFIKASI, DAN GIBERELIN PADA PERKECAMBAHAN EMBRIO APEL - Bambang S. Purwoko; Loyd E. Powell (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
The objective of the present experiment was to determine the inhibitory properties of short chain fatty acids (SCFA) in apple embryo germination. The result showed that the SCFA inhibition on apple embryo germination was dependent on chain length and was in the millimolar range. No synergistic effect was observed when SCFA were applied simultaneously. The inhibition of SCFA was reversed by GA4+7. A higher concentration of SCFA was needed to inhibit embryo germination as the stratification progressed.